Freshwater ichthyofauna of wetlands in Tablas Island, Romblon, The Philippines - Gonzalez, Jeric B.; Gado, Vincent Jay H.; Mantes, Bernie G. (Academia Journal of Biology, 2023)
The Philippines is a hotspot for biological variety and a hub for endemism on a worldwide scale. Despite this, most of the research has focused on terrestrial and marine biodiversity, with little knowledge of freshwater fish diversity and status. There has been no systematic research on these species in Romblon. As a result, this research was conducted. This study aims to evaluate the freshwater fishes of Tablas Island, Romblon, utilizing modified hoop nets, gill nets, scoop nets, and hook and line. A total of 44 species belonging to 36 genera and 19 families were identified. They are often found in rivers, and streams, while most of them are native to the Philippines, where they are being eaten by natives. The IUCN Red List placed the majority of these species in the Least Concern category. The dominating species was Gambusia affinis, with Giuris margaritaceus being the most frequent across all sites. A new locality record of an indigenous minnow species (Barbodes hemictenus) was found. The ichthyofauna of Tablas Island is diverse, with local species dominating. Only two introduced species were identified as threatened (Vulnerable). On the other hand, the rest were classified as Least Concern, Unknown, Not Evaluated, and Data Deficient.